Giant anisotropic magnetoresistance and nonvolatile memory in canted antiferromagnet Sr2IrO4 - Haowen Wang (Nature Portfolio, 2019)
The determination of the antiferromagnetic (AFM) orders by the anisotropic magnetoresistance (AMR) is one of the key components to the AFM-spintronics. Here the authors report enhanced AMR ~160% in Sr2IrO4 due to the combination of atomic scale giant-MR-like effect and magnetocrystalline anisotropy energy.